Analisis Hukum terhadap Pertanggungjawaban Pidana Pelaku Penggelapan Pajak Pertambangan - Sukma, Intan Selvian; Pohan, Masitah (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
In the world of mining, the reality is often inseparable from the challenge of tax evasion. This practice can harm a country's economy, hinder development, and create inequality in wealth distribution. The purpose of this study is to determine the definition and elements of the criminal act of tax evasion in the context of mining, how criminal responsibility is imposed on the perpetrators of mining tax evasion based on applicable laws and regulations, and the impact of mining tax evasion on the country's economy and society. The method used in this research is to use normative legal research methods, especially library legal research. This research is based on the use of library materials as the main source of information. The results of this study found that tax evasion in the context of mining refers to deliberate actions to avoid or reduce tax payments that should be paid to the state, in violation of tax laws. In Law Number 28 Year 2007, the criminal offense of tax evasion, mainly described in chapter VIII article 38 to article 43, details the handling steps and sanctions for perpetrators. If someone is involved in tax evasion, the handling will refer to the provisions of the tax law, especially article 38. Tax evasion in the mining sector can have serious impacts on the country's economy and society. The impacts include a reduction in state revenue, inhibition of infrastructure development, socio-economic inequality, a potential decrease in investment, an increase in the tax burden for the compliant, a decrease in public trust, environmental impacts, and potential difficulties in law enforcement.